DETERMINATION OF CORPORATE RISK MANAGEMENT APPLICATION LEVEL: A SURVEY IN MANISA PROVINCE - Burcu KOCARIK GACAR; Anıl GACAR (Dokuz Eylül Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2021)
ABSTRACT: In this study, it was aimed to research the levels of corporate risk management application in businesses operating in Manisa. For this purpose, a survey was conducted to investigate the awareness of corporate risk management of businesses in Manisa Organized Industrial Zone. The survey results were evaluated by multidimensional scaling and correspondence analysis. Corporate risk management managers of 56 businesses participated in the survey. According to findings, it is found that the corporate risk management practices of businesses are at Level 4, but there is a lack in which guidance or standard is adapted. Also, while corporate risk management can be mentioned as a formal and rules-based risk management process in businesses carried out by internal auditors, it is observed that there is no specific risk management process in businesses where other (board of directors, CEO, human resources, occupational health, and safety specialist, external support) are responsible. Besides, it is determined that there are no businesses with the COSO corporate risk management guidance published by the United States that could be adapted to large businesses among the businesses that responded to the survey. ÖZ: Bu çalışmada, Manisa’da faaliyet gösteren işletmelerde kurumsal risk yönetimi uygulama düzeylerinin araştırılması amaçlanmıştır. Bu doğrultuda, Manisa Organize Sanayi Bölgesi’ndeki işletmelerin kurumsal risk yönetimi farkındalığını araştırmak amacıyla anket uygulanmıştır. Ankete 56 işletmenin kurumsal risk yönetimi yöneticileri katılmıştır. Anket sonuçları çok boyutlu ölçekleme ve uyum analizi yapılarak değerlendirilmiştir. Çalışmada elde edilen bulgulara göre, işletmelerin kurumsal risk yönetimi uygulamalarının Düzey 4 seviyesinde olduğu; ancak bu sürecin bir rehber ya da standarda uyarlanması konusunda bir eksiklik olduğu tespit edilmiştir. Ayrıca, kurumsal risk yönetimi süreci, iç denetçiler tarafından yürütülen işletmelerde resmi ve kurallara dayalı bir risk yönetim süreci olup diğer sorumluların (yönetim kurulu, CEO, insan kaynakları, iş sağlığı ve güvenliği uzmanı, dış destek) olduğu işletmelerde özel bir risk yönetim süreci uygulaması olduğu belirlenmiştir. Ayrıca, ABD tarafından yayınlanan COSO kurumsal risk yönetimi rehberine ankete katılan büyük işletmelerden hiçbirinin sahip olmadığı tespit edilmiştir